REGULATORY CAPTURE OF THE HIGHER EDUCATION AREA: THE ANALYSIS OF SOME ASPECTS - Ekaterina I. Trubnikova (Высшее образование в России, 2016)
The article investigates certain aspects of the national higher education system of Russian Federation. Special attention is paid to the presence of formal and informal mechanisms that facilitate the capture of regulation and rent extraction by the existing actors. The article presents an analysis of possibilities of opportunistic behavior of the administration of a higher education organization. As a source of the rent there might be inappropriate use of the institutions facilitated by the various mechanisms. In this case this source can be warranted by the internal regulatory documents of the organizations, as well as the external legal statutes. The research also presents analysis of rent extraction sources and examples of the use of administrative resources. The article points out the negative trends and growth of opportunities of rent-seeking behavior of the actors of this market.